2021
DOI: 10.1590/2177-6709.26.5.e212042.oar
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution analysis in anterior teeth caused by several retraction mechanics

Abstract: Introduction: Orthodontic retraction of the anterior teeth is indicated when the patient has a malocclusion with protrusion of the incisors. Several mechanics are indicated to perform this retraction. Objective: The objective of this study was to compare the strains generated by four different types of retraction mechanics along the roots of the anterior teeth. Methods: A photoelastic model simulating an arch with first premolars extraction was made. Sixty retraction archwires were prepared, including fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…From the above-mentioned study, we can say that Figure 1 where retraction was carried out from mini-implant to the arch wire hook can help in achieving bodily tooth movement without the loss of anchorage, can be achieved. Domingos et al 14 found that stress was concentrated on the canine region. Lee et al 15 in their study stated that an absolute anchorage tends to decrease the stress on the posterior aspect of the teeth and concentrates on the roots of the anterior teeth as well.…”
Section: Discussionmentioning
confidence: 99%
“…From the above-mentioned study, we can say that Figure 1 where retraction was carried out from mini-implant to the arch wire hook can help in achieving bodily tooth movement without the loss of anchorage, can be achieved. Domingos et al 14 found that stress was concentrated on the canine region. Lee et al 15 in their study stated that an absolute anchorage tends to decrease the stress on the posterior aspect of the teeth and concentrates on the roots of the anterior teeth as well.…”
Section: Discussionmentioning
confidence: 99%
“…Added advantages of this type of archwires are that it prevents the undesirable tilting of the molars and rotation of the premolars and it has a mild impact on the anterior teeth that will not cause pain to patients. Aside from that, the 3D control over these wires is available since the start of treatment [27][28][29][30].…”
Section: Tri-force Wiresmentioning
confidence: 99%